ECONOMIC AND DEMOGRAPHIC DETERMINANTS AND ITS EFFECT ON CONSUMER PURCHASING DECISION IN THE NIGERIAN AUTOMOBILE INDUSTRY - Koce, Henry Diko; Ndaba, Mamman Zacchaeus; Gata, Elizabeth Gabriel (International Journal of Research -GRANTHAALAYAH, 2021)
Consumers are likely influenced by so many factors among them are demographic variables and economic variables, this is important especially in decision of capital expenditure such as the purchase of automobiles. This study investigated the demographic determinant of consumer purchase decision in the Nigeria Automobile industry. This study employed the use of survey method as well as descriptive analysis, by which consumers opinion where sampled. The population of the study car owners residing in Niger state with total car population of 508, 564(NGSDVR, 2012). The sample size of 1110 was determined through formula, plus mark up of 30% margin of non-response which totaled to one thousand four hundred and forty-three respondents. One thousand one hundred questionnaires were filled and returned. To ensure reliability of research instrument was conducted and the result of Cronch Bach alpha was .887 which is greater than. 70 Regression and correlations analysis was used to analyze the data collected with the aid of the statistical package (SPSS). Hypothesis one result showed a significant relationship between demographic variable and consumer purchase decision of automobile (R2 =. .968) and P value of.000, finally hypothesis two indicated that economic variables have a great influence on consumer purchase decision of automobiles (R2 =. .970) and P value of.000. Recommendations was that procedures should take all these variables into consideration in designing products and advertising.